Making the American religious fringe : exotics, subversives, and journalists, 1955-1993 - McCloud, Sean (University of North Carolina Press, 2004)
In an examination of religion coverage in Time, Newsweek, Life, The Saturday Evening Post, Ebony, Christianity Today, National Review, and other news magazines, Sean McCloud combines religious history and social theory to analyze how and why mass-market magazines depicted religions as "mainstream" or "fringe" in the post-World War II United States